(untitled) - Guell, C. Robert (Boston, 2007)
Issues in Economics Today is a modern issues book that presents the latest and most interesting topics. Most importantly, this title was developed to allow instructors the maximum flexibility to teach this material in a manner that fits their personal style.
Keywords: Economics,Kinh tế học